Hubungan Antara Job Crafting dan Meaningful Work dengan Organizational Citizenship Behavior - Raden Roro Shahsya Wulan Putri Widyadari (CV. ITTC INDONESIA, 2026)
Organizational Citizenship Behavior is a voluntary behavior that contributes positively to organizational effectiveness and success. This study aimed to examine the relationship between Job Crafting and Meaningful Work, both simultaneously and partially, with Organizational Citizenship Behavior among employees of the Human Resource Development Department and the Organization and Position Department at PT Petrokimia Gresik. This study employed a quantitative approach with a correlational research design. The population consisted of 106 employees. Data were collected using Likert scales to measure Organizational Citizenship Behavior, Job Crafting, and Meaningful Work, all of which had met the validity and reliability requirements. The data were analyzed using multiple linear regression with IBM SPSS Statistics version 27. The results showed that Job Crafting and Meaningful Work simultaneously had a significant relationship with Organizational Citizenship Behavior (R = 0.782; F = 81.967; p < 0.001), with a contribution of 61.4%. Partially,Job Crafting had a positive and significant relationship with Organizational Citizenship Behavior (β = 0.327; t = 3.591; p < 0.001). Meaningful Work also had a positive and significant relationship with Organizational Citizenship Behavior (β =0.510; t = 5.598; p < 0.001). The coefficient of determination (R²) of 0.614 indicates that Job Crafting and Meaningful Work jointly explained 61.4% of the variance in Organizational Citizenship Behavior, while the remaining 38.6% was influenced by other factors beyond the scope of this study. These findings indicate that Meaningful Work contributed more strongly than Job Crafting in explaining Organizational Citizenship Behavior among employees. Therefore, organizations are encouraged to foster a work environment that enhances employees' sense of meaningful work and provides opportunities for employees to engage in Job Crafting in order to promote Organizational Citizenship Behavior.